Nondestructive evaluation : theory, techniques, and applications - Shull, Peter J., 1957- (M. Dekker, 2002)
Describing NDE issues associated with real-world applications, this comprehensive book details conventional and forthcoming NDE technologies. It instructs on current practices, common techniques and equipment applications, and the potentials and limitations of current NDE methods. Each chapter details a different method, providing an overview, an explanation of the fundamental physical laws governing the method, the inspection techniques and typical equipment used in it's application, final system integration of transducers, supporting instrumentation, commonly practiced procedures necessary f.
Keywords: Nondestructive testing.; elektronické knihy; electronic books